Social responsibility : analysis of the approach of ISO 26000 - Andía Valencia, Walter (2015)
The development of business activities from a holistic perspective involves a set of social impacts, which must be included in the management of organizations, so, that has developed an International Standard providing guidelines for social responsibility (RS) called ISO 26000. The following article has as objective analyze the conceptual approach to social responsibility by ISO and to propose a change of approach to define in an appropriate manner the responsibilities of business..